2010
DOI: 10.3851/imp1552
|View full text |Cite
|
Sign up to set email alerts
|

Development of HBV S gene mutants in chronic hepatitis B patients receiving nucleotide/nucleoside analogue therapy

Abstract: Structurally modified nucleotide/nucleoside analogues can exert potent inhibitory effect on HBV polymerase activities. Some of these agents have been approved for the treatment of chronic hepatitis B. Because of a high risk of reactivation upon drug withdrawal, continuous long-term therapy is recommended to maintain maximal viral suppression. Consequently, drug resistance has developed in a significant proportion of patients. During long-term therapy, mutations occur not only in the polymerase gene but also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…Antiviral-drug-associated S gene mutations (ADASMs) can lead to three different consequences [112] : amino acid substitution mutations in the surface proteins, nonsense mutations resulting in truncated surface proteins and silent mutations. Also, there are ADASMs that cannot be explained by gene overlapping but which are probably the result of lower or reverse ratio of HBsAg to anti-HBs during long-term efficient viral suppression.…”
Section: Mutationsmentioning
confidence: 99%
“…Antiviral-drug-associated S gene mutations (ADASMs) can lead to three different consequences [112] : amino acid substitution mutations in the surface proteins, nonsense mutations resulting in truncated surface proteins and silent mutations. Also, there are ADASMs that cannot be explained by gene overlapping but which are probably the result of lower or reverse ratio of HBsAg to anti-HBs during long-term efficient viral suppression.…”
Section: Mutationsmentioning
confidence: 99%
“…Furthermore, the rtL180M mutation emerged at time point 3 in correlation with the rtS143T mutation, which corresponds to the S gene sF134L mutation. Because the S gene is overlapped by the polymerase gene, whenever a nucleotide mutation occurs in the polymerase gene, a concomitant nucleotide mutation develops in the S gene (14). The mutation in sF134L/rtS143T emerged based on the following two main possible explanations: the sF134L mutation induced by host immune pressure forced the development of the rtS143T mutation and the lamivudine-resistant rtS143T mutation forced the development of the sF134L mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This point mutation was recently reported in CHB patients with viral breakthrough after LMV or ADV treatment (5)(6)(7)(8)(9). Recent studies have indicated that the rtA181T/sW172* mutant has a dominant negative secretion effect as well as an increased oncogenic potential through its transactivation activity (4,(10)(11)(12)(13). It can also be speculated that is these truncated proteins cause endoplasmic reticulum (ER) stress and cell damage by intracellular retention (12,14).…”
Section: Introductionmentioning
confidence: 91%
“…Consequently, mutations in the polymerase gene may produce changes in the overlapping S gene, which confer resistance against NAs. Widespread treatment of CHB infection with NAs results in the selection of these resistant HBV mutants, thus causing serious public health implications (3,4).…”
Section: Introductionmentioning
confidence: 99%